Bulima interventions via interpersonal influence: the role of threat and efficacy in persuading bulimics to seek help. - Smalec JL; Slingle RS (Journal of Behavioral Medicine, 2000)
The causes and medical consequences of bulimia are well established in the literature, yet prevalence rates for bulimia continue to be quite high. Eating disorder books and popular magazines have offered a variety of ways in which individuals can communicatively influence bulimics to seek the help they need to treat their disorder. Unfortunately, many of the recommended influence strategies have been atheoretically derived and sorely lack empirical data affirming their effectiveness. The present study investigates and empirically tests the effectiveness of interpersonal intervention messages aimed at getting bulimic individuals to seek medical help. Several theoretical perspectives, as they relate to messages of threat and efficacy, were used to predict the effects of bulimics' threat and efficacy perceptions on message acceptance and message rejection. A main and positive effect for efficacy was found on message acceptance. A threat by efficacy interaction on message acceptance was partially supported for both cognitive and behavioral message acceptance. The threat by efficacy interaction was not significant for message rejection. Overall, this study confirmed the notion that high levels of both threat and efficacy are necessary to convince bulimic individuals to seek help. These findings can be used to aid concerned individuals in their quest to intervene and to get bulimics to seek out the necessary medical assistance and support.